ANALISIS PENGARUH E-RECOVERY SERVICE QUALITY DAN CUSTOMER EXPERIENCE PADA CHATBOT TERHADAP KEPUASAN KONSUMEN E-COMMERCE SHOPEE DI KOTA BATAM - Mia Syafrina; Iga Puri Permata (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This study aims to analyze the effects-recovery service quality and customer experience on chatbots on consumer satisfaction with e-commerce shop in Batam City. The method used in this study is a survey by distributing research questionnaires through social media to 100 respondents who fit the criteria, resulting in quantitative data which will later be compiled using Microsoft Excel and then processed using a statistical application, namely Statistical Product and Service Solution (SPSS 23). This study used multiple linear regression analysis techniques which went through several stages of research, namely the research instrument test, the classical assumption test, and the research hypothesis test. The results obtained are variables-recovery service quality and variables customer experience on chatbots significantly influence shopee customer satisfaction in Batam City both partially and simultaneously.